Analysis of Student Knowledge About Basic Teaching Skills at PGSD FKIP UNRI - Munastri Qodri; Gustimal Witri (Yayasan Thaifah Manshurah Pekanbaru, 2024)
A teacher needs to master basic teaching skills in carrying out learning activities. Basic teaching skills are one of the characteristics of a teacher in developing the learning activities carried out, this can be realized through action. The aim of this research is to describe and identify the knowledge of PGSD FKIP UNRI students regarding basic teaching skills. In this research, a qualitative research design was used, with a descriptive method that focused on analyzing student knowledge about basic teaching skills in the FKIP UNRI Primary School Teacher Education Study Program. Data collection techniques using observation, interviews and documentation. The data analysis techniques used in this research are data reduction, data presentation and drawing conclusions. The research results revealed that the majority of PGSD FKIP UNRI students counted in the class of 2019 had sufficient knowledge of basic teaching skills. During their study journey, students also need to pay more attention to developing basic teaching skills, especially in terms of using learning media and evaluating learning